An inter-laboratory stability study of roll-to-roll coated flexible polymer solar modules - Gevorgyan, Suren A.; Medford, Andrew J.; Bundgaard, Eva; Sapkota, Subarna B.; Schleiermacher, Hans-Frieder; Zimmermann, Birger; Wuerfel, Uli; Chafiq, Amine; Lira-Cantu, Monica; Swonke, Thomas; Wagner, Michael; Brabec, Christoph J.; et al. (ELSEVIER SCIENCE BV, 2011)
A large number of flexible polymer solar modules comprising 16 serially connected individual cells was prepared at the experimental workshop at Riso DTU. The photoactive layer was prepared from several varieties of P3HT (Merck, Plextronics, BASF and Riso DTU) and two varieties of ZnO (nanoparticulate, thin film) were employed as electron transport layers. The devices were all tested at Riso DTU and the functional devices were subjected to an inter-laboratory study involving the performance and the stability of modules over time in the dark, under light soaking and outdoor conditions. 24 laboratories from 10 countries and across four different continents were involved in the studies. The reported results allowed for analysis of the variability between different groups in performing lifetime studies as well as performing a comparison of different testing procedures. These studies constitute the first steps toward establishing standard procedures for an OPV lifetime characterization. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: DEGRADATION; WATER